Consistent effects of empagliflozin on cardiovascular and kidney outcomes irrespective of diabetic kidney disease categories: insights from the EMPA-REG OUTCOME trial - Wanner, Christoph; Inzucchi, Silvio E.; Zinman, Bernard; Koitka-Weber, Audrey; Mattheus, Michaela; George, Jyothis T.; Eynatten, Maximilian von; Hauske, Sibylle J. (Diabetes, obesity and metabolism, 2020)
Abstract Aim To explore the cardiovascular (CV) and kidney effects of empagliflozin in patients with different clinical phenotypes of diabetic kidney disease (DKD) (i.e. with the presence or absence of overt albuminuria) participating in the EMPA-REG OUTCOME trial. Materials and methods EMPA-REG OUTCOME randomized participants (1:1:1) to empagliflozin 10 mg, 25?mg or placebo, added to standard of care. Post hoc, patients with different clinical phenotypes of DKD at baseline were categorized in three subgroups: (a) overt DKD (overt albuminuria [urinary albumin-to-creatinine ratio of >300?mg/g] with any estimated glomerular filtration rate [eGFR]; n = 769); (b) non-overt DKD (kidney impairment [eGFR .05), consistent with the overall trial population findings. Empagliflozin also significantly reduced the yearly loss of eGFR, assessed by chronic slopes, in all subgroups. The adverse event profile of empagliflozin was similar across all subgroups. Conclusions Empagliflozin may improve CV and kidney outcomes and slow the progression of kidney disease in type 2 diabetes patients with DKD, irrespective of its clinical form, both with or without the presence of overt albuminuria.